MPT : management decision-making at an automotive parts supplier - Kleinsmith, Niela; Koene, Bas, 1966-; Latniak, Erich (London : Rotterdam School of Management, Erasmus University, 2018)
In October 2017, Henry Novak, Plant Manager for MPT (Moulded Plastic Technologies), a mid-sized, family-owned, European automotive supplier, walked across the shop floor during his regular '2018;caravan' morning tour with his senior team. Since the global financial crisis, when MPT's family-owners had appointed a new general manager, the company had undergone major restructuring and was slowly making a comeback from the brink of bankruptcy. But with the disruptive changes occurring in the automotive industry, MPT still had a long way to go to secure its future. In particular, executive management was trying to resolve two divisive issues: (1) should the company make substantial investments in more automated production equipment; and (2) how could the company better respond to request for quotations (ROQs) from original equipment manufacturers (OEMs), as response times and details were often insufficient? Walking around the shop floor, Novak had the answers to both of these questions, and was looking forward to the management meeting later in the day to present his arguments.
Originally Published In Kleinsmith, N., Koene, B., & Latniak, E. (2018). MPT: Management Decision-Making at an Automotive Parts Supplier. Rotterdam, Netherlands: Rotterdam School of Management, Erasmus University.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Decision making; Industrial management; Automobile industry and trade -- Management